Fare parchi urbani - Anna, Lambertini (Scuole di dottorato, 2006)
The work addresses the subject of the contemporary urban park, interpreted as an ethical and aesthetic space. Ethical in the proper sense of the word, that is conforming to the character of the place, and aesthetic in the sense of an urban space subject to qualitative valuations and the ambit of production of aesthetic experience in a real environment animated by the presence of nature. Tracing a critical itinerary through the history of the art of parks and gardens and the current trends of landscape architecture in Europe, the book sustains the theory that the ethics of creating parks always implies a meditation on aesthetic principles and values. The variety of current production is read through several original keys to interpretation: an historic overview of the ethical and aesthetic models, the identification of species of parks and the definition of ethical/aesthetic categories. The final section proposes a modus operandi that adopts the narrative dimension as a guideline for design. Published in the volume is the doctoral thesis that received the Grinzane Cavour - Giardini Hanbury special prize in 2006.